2007
DOI: 10.1111/j.1537-2995.2007.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

HPA‐1a antibody potency and bioactivity do not predict severity of fetomaternal alloimmune thrombocytopenia

Abstract: Neither severe thrombocytopenia nor ICH in HPA-1a-alloimmunized pregnancies can be predicted with sufficient sensitivity and specificity for clinical application from maternal anti-HPA-1a potency or bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 34 publications
2
48
2
1
Order By: Relevance
“…Recently, Ghevaert et al 10 published the results of a retrospective study in which no correlation could be found between the maternal anti-HPA 1a antibody level and platelet count in the neonates. The explanation for the divergence between their results and ours may be differences in selection criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ghevaert et al 10 published the results of a retrospective study in which no correlation could be found between the maternal anti-HPA 1a antibody level and platelet count in the neonates. The explanation for the divergence between their results and ours may be differences in selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] A correlation was also found in two retrospective studies, 8,9 whereas one other retrospective study did not find such a relationship. 10 In a recent trial, we documented that identification of women with anti-HPA 1a antibodies, close clinical follow-up during pregnancy, elective Cesarean section and transfusion of compatible platelets to neonates with severe thrombocytopenia, reduce NAIT-related morbidity and mortality. 11 The main purpose of this study was to describe the natural course of HPA 1a alloimmunity by recording maternal anti-HPA 1a antibody levels longitudinally throughout pregnancy and after delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In hemolytic disease of the newborn, clinically significant hemolysis is associated with CL responses of more than 30% of the maximum response obtained with a control antibody (48). With HPA-1a antibodies, there appears to be no correlation between either in vitro potency or monocyte CL responses to maternal anti-HPA-1a and fetal platelet count (53). Therefore, at this stage it would be difficult to estimate by how much maternal antibodies would have to be blocked to generate a clinically significant effect.…”
Section: Figurementioning
confidence: 97%
“…The potency of each clinical sample and both polyclonal IgG preparations was measured using the international anti-HPA-1a potency standard 03/152 (100 IU/ml) (National Institute for Biological Standards and Control) (53,58).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, maternal anti-HPA-1a antibody level during the pregnancy has been claimed to be a better predictive factor, although the predictive value has been questioned [48]. Williamson et al reported a correlation between antibody titre in the last trimester and severity of thrombocytopenia [10].…”
Section: Antibody Level As a Predictor Of Severitymentioning
confidence: 99%